Planning and Management of Water Resources in the Context of Economic Devlopment and Climate Change in Algerian Highlands by the Weap Model, Case of the Gareat El Tarf Basin (Northwestern Algeria) - Dali, Naouel (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Water in the Gareat El Tarf basin, is affected by climatic and economic constraints; while its development is based on the agricultural sector, which creates pressure on water resources. The objective of this study is to analyse the performance of the national water plan to accompany this policy, and the impact of climate change on water resources.
Keywords: Gareat El Tarf basin; WEAP; climate changes; water resources; water management; dorzecze Gareat El Tarf; zmiany klimatu; zasoby wodne; gospodarka wodna